Implementasi Sanksi Terhadap Para Pelanggar Protokol Kesehatan Di Masa Pandemi Covid-19 Menurut Instruksi Presiden Nomor 6 Tahun 2020: (Study Kasus Kecamatan Kraksaan Kabupaten Probolinggo) - Kholidazia El HF.; Nur Aini (STIH Zainul Hasan Kraksaan Kraksaan, 2021)
Presidential Instruction Number 6 of 2020 concerning Improvement of Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019 (Covid-19), is a policy that has been made by the government in response to the increasing spread of the COVID-19 virus that is currently hitting Indonesia. In following up on Presidential Instruction No. 6 of 2020, the Probolinggo Regency Government stipulates Probolinggo Regent Regulation No. 62 of 2020 on Increasing Discipline and Enforcement of Health Protocol Laws in the Prevention and Control of Corona Virus Disease 2019 (Covid-19). The problems that the authors examine in this study and their objectives are to find out how legal action is taken for people who violate health protocols, secondly to determine the effectiveness of the implementation of sanctions that have been carried out by the Covid-19 Task Force of Kraksaan District. Based on the formulation of the problem and the research objectives, the method used by the author is an empirical juridical approach, namely legal research on those governing Health Protocols related to implementation by the government and the Kraksaan District Covid-19 Task Force. The results of the research in the preparation of this thesis, the first factors that cause violations of health protocols. Second, law enforcement for people who violate the Health Protocol. Third, the effectiveness of the application of sanctions for health protocol violators based on the applicable legal regulations in the Probolinggo Regency area. Keyword: Covid-19, Health Protocol, Law Enforcement Prokes